Associação genética entre habilidade de permanência no rebanho em partos consecutivos e características de interesse econômico em bovinos nelore - Morales, Débora da Silva (2021)
The trait stayability (STAY) is a way of assessing the female's longevity potential. Measuring the STAY to each cow calving would allow obtaining earlier indicators of longevity. The objective with the present study was to estimate genetic parameters for STAY in consecutive calvings, age at first calving (AFC), days to calving (DC), weaning weight (WW), and yearling weight (YW); the possible genetic association between the STAY in consecutive calvings and AFC, DC, WW and YW; the influence of the animals genetic potential for the traits AFC, DC, WW and YW in the chances of selection for STAY in consecutive calvings in Nellore cattle. The estimation of variance components and subsequent prediction of breeding values was performed through single-trait analyzes. The estimated breeding values (EBV) were then used to analyze the association between STAY and the other traits. For HPR in consecutive calvings, the heritability estimates ranged from 0.02 to 0.06, with an increasing magnitude according to the calving number. For the traits AFC, DC, WW (direct and maternal effects), and YW, the heritability estimates were 0.07, 0.02, 0.17 and 0.08, 0.33, respectively. Genetic correlation estimates between STAY in different calvings ranged from 0.58 to 0.94 and were higher between closer calvings. The correlation estimates between EBV of the intercept coefficient for STAY in consecutive calvings and EBV of AFC, DC, WW (direct and maternal effects), and YW were -0.14, -0.08, 0.05 and 0.005, 0.07, respectively. The influence of genetic potential of reproductive traits on the odds ratio of selection for STAY in consecutive calvings resulted in a decrease in the chance of selection for STAY in all calvings studied when the EBV for AFC or DC were increased. The WW (direct effect) positively influenced the selection for STAY initially and negatively influenced it at the end of the cow's reproductive life. The WW (maternal effect) positively influenced the scenario with greater selection intensity and negatively influenced it in the other scenarios. For the YW, an increase in genetic potential increased the chances of selection for STAY, except for the later calvings of the scenario with greater selection intensity.